The Influence of Consumer Behavior on Purchasing Decisions - Lase, Enifarmawati; Zebua, Emanuel; Mendrofa, Yupiter; Hulu, Perlindungan F. (Golden Ratio of Data in Summary, 2024)
Retail trade is a very strategic trade in Indonesia because it is able to absorb labor after the agricultural sector. There are two types of retail trade, namely traditional retail which is directly represented by small traders or grocery traders in traditional markets and in housing and modern retail which is represented by supermarkets and minimarkets such as Alfamart and Indomaret. This proves that there is quite high economic growth and creates investment, but on the other hand, this can cause lethargy for traditional kiosk traders, even killing their businesses. Yuki Mart is one of the modern shops (minimarkets) in Gunungsitoli City. This research aims to find out how much influence consumer behavior has on purchasing decisions at Yuki Mart, Gunungsitoli City. This research uses quantitative methods. Respondents were 57 consumers who shopped at Yuki Mart, Gunungsitoli City in July, where researchers collected data using a questionnaire, then carried out data validity tests, data reliability tests, classical assumption tests (normality tests), coefficient of determination, and hypothesis tests (t tests). The results of the research show that the influence of consumer behavior on purchasing decisions at Yuki Mart, Gunungsitoli City, is 16.3% and the other 83.7% is influenced by other variables not included in this research.